Long-term investigation of pollutant removal efficiency in two constructed wetlands for wastewater treatment and reuse in urban areas - Farruggia, Davide; Licata, Mario; Leto, Claudio; Urso, Giovanni; Salamone, Francesco; Sousa Coutinho Calheiros, Cristina (Frontiers in Environmental Science, 2025)
Constructed wetland (CW) systems offer many advantages for wastewater treatment in urban areas and are increasingly seen as sustainable solutions. However, their pollutant removal capacity can vary significantly, influenced by weather conditions and the specific plant species used. This paper presents a long-term study conducted on two pilot-scale horizontal subsurface flow (HSSF) CWs located in two different towns of Sicily (Italy). The main aims were to compare the pollutant removal efficiency (RE) of two HSSF CWs treating urban wastewater and to assess the effect of treated wastewater (TWW) reuse on bermudagrass [Cynodon dactylon (L.) Pers.] traits and soil characteristics. The two CWs had comparable surface areas and were each planted with a different species, resulting in monoculture systems. Two experimental fields of bermudagrass were set up, one for each HSSF CW. The effects of 3 years and two sources of irrigation water [TWW and freshwater (FW) as control] were assessed using a split-plot design for two-factor experiments. Results highlight that removal efficiencies up to 83% were achieved for an inlet of 55 ± 14 mg COD L−1, 81% for an inlet of 31 ± 5 mg BOD5 L−1, 66% for an inlet of 20.6 ± 3.5 mg total nitrogen L−1, and 50% for an inlet of 7.9 ± 0.8 mg total phosphorus L−1. Both CW systems demonstrated effective long-term performance in the removal of physico-chemical and microbiological contaminants. Bermudagrass had higher above-ground biomass production (1,358.74 kg ha−1) in TWW-irrigated plots than those plots irrigated with FW (1,005.98 kg ha−1), on average. The highest biomass yields were recorded during the second and third years of the study. Visual turf quality ratings were consistently similar across years and irrigation treatments. No significant variations in soil pH were observed between FW- and TWW-irrigated soils. However, soils irrigated with TWW showed higher salinity, organic matter, macronutrients, and sodium levels, on average.